(untitled) (Bangladesh Journal of Medicine, 2013)
Background: The aim and objective of this study was to evaluate relationship of serum albumin and esophageal varices in chronic liver disease (CLD) admitted in the medicine unit and gastroenterology department of Dhaka Medical College Hospital. Method: In this cross-sectional study, a total number of 100 randomly selected, clinically diagnosed patients of chronic liver disease were studied from June 2010 to November 2010 (6 months). All patients were assessed as per Child-Pugh class and had full blood count, HBsAg, Anti-HCV antibodies by ELISA, abdominal ultrasound and Endoscopy of upper gastrointestinal tract. Patients were divided into Group A (serum albumin <3.5 gm%) and Group B (3.55). Result: Seventy-three male (73%) and twenty seven female patients (27%)] with age range of 16 to 75 years were evaluated. Out of 100 patients 24% were in between 46-55 years age group. 63% patient fall in child Pugh class A group, 32% fall in child Pugh class B & 5% fall in child Pugh class C. Mean Serum albumin was 3.8 gm%, (range 2.4-4.9). Esophageal varices (EV) were present in 32 patients (32%) and absent in 68 patients (68%). Group A had 29 patients (29% of the total) with 18 patients (62.06%) having EV. Group B had 71 patients (71% of the total) with 14 patients (19.71%) having EV. Sensitivity of hypoalbuminaemia as a marker of EV was 56% and specificity 83.8%, positive predictive value 62.06% and negative predictive value 80.2% and Odds ratio was 6.6. P value is <0.001. Conclusion: In Group A that is hypoalbuminaemia (<3.5 gm%), the incidence of Esophageal varices was more than Group B that is albumin level (>3.5gm%). Hypoalbuminemia is a good surrogate marker for the presence of esophageal varices in CLD. DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13595 Bangladesh J Medicine 2011; 22: 17-20